TINJAUAN TENTANG EFISIENSI BAHAN OLAHAN DI DAPUR HOTEL DAFAM FORTUNA SETURAN YOGYAKARTA - Saldinsih, Oktavia; Rochanawati, Ida (Jurnal Pariwisata Bunda, 2023)
This article reports on the results of research on the efficiency of processed ingredients in the kitchen department. data were obtained through observations, questionnaires, and documentation. The efficiency of processed ingredients is the level of resource use in processing processed ingredients in the production process. The more economical the processed ingredients are to eat the processed ingredients, the more efficient.Thus, the kitchen department should emphasize that the processed ingredients that enter the kitchen must be used efficiently. Efficiency is beneficial to carry out resource savings. The goal of implementing efficiency is to maximize the use of resources and minimize unnecessary waste.